The Effect Of Career Development And Work Lıfe Balance Toward Intentıon To Stay On Generatıon Z In Bandung Raya - Putri Azzahra Febriyanthy; Fetty Poerwita Sary (Cita Konsultindo Research Center, 2024)
The purpose of this study is to examine the relationship between career development and intention to stay in Generation Z in the Bandung Raya area, and the relationship between work life balance and intention to stay in Generation Z in the Bandung Raya area. The study used a quantitative research method. The population of the study was Generation Z in the Bandung Raya area, with a sample size of 150 respondents. Non-probability sampling with purposive sampling was used to select the sample. Descriptive analysis and structural equation modeling-partial least squares (SEM-PLS) analysis were used to analyze the data. The results of the study showed that career development has a significant and positive effect on intention to stay. Work life balance also has a positive effect on intention to stay. In other words, the better the career development and work life balance in a company, the higher the intention to stay or the desire of Generation Z employees to stay with the company.